THE PRINCIPAL – DESIGN AND DEVELOPMENT OF AN INTERACTIVE FILM-GAME ON SCHOOL LEADERSHIP - Atienza, Ethel Joan (Universitas Terbuka, 2023)
The paper presents work on a tablet-based and smartphone-based game for school heads and other education stakeholders. The paper highlights the design and development of an interactive film-game on school leadership with regard to its content, storyline, film execution, and leadership game scoring framework. The paper discusses how these elements combine to elicit engagement, reflection, and discussion among players and the possibilities it presents for school leadership capacity building.